Income, consumption pattern and economic status of paddy farming household (with special reference to sammanthurai divisional secretariat area) - Lebbe, S.M.A. (University of Jaffna, 2012)
Nearly 70 percent of total population living in rural areas depends completely or partially on agriculture sector. Sri Lanka has made great strides in the sphere of agricultural development in general and paddy cultivation in particular. The main objective of the study is to examine income, consumption pattern and economic status of paddy farming households in the study area. Primary data related to the year 2009-2010 were collected from 280 paddy farmers from four types of paddy cultivation groups. Food ratios for all farming households are more than 50 percent of their total expenditure. Further, the average loan per household and per capita indebtedness, followed by the interest payments for the loans of the paddy farmers, is extremely higher. On the other hand, it is noteworthy to point out that the expenditure, income and debt are higher to all categories of paddy farmers. Hence, policy makers should pay attention to increase their income especially from paddy cultivation and also to raise purchasing power of paddy farming community in Sri Lanka.
Keywords: Consumption; Economic status; Food ratio